A high-energy, low-temperature lithium-sulfur flow battery enabled by an amphiphilic-functionalized suspension catholyte. (December 2020) - Xu, S.; Zhang, L.; Zhang, H.; Wei, M.; Guo, X.; Zhang, S.
Abstract: Lithium-sulfur flow batteries show great superiority in large-scale energy storage. However, the sulfur utilization in high sulfur loading suspension catholyte declines sharply due to the insulating nature of sulfur/sulfides. Adding more carbon conductive materials can augment sulfur utilization, while high carbon content limits the specific energy and meanwhile increases the viscosity of suspension catholyte. In this work, a high-energy, low-temperature sulfur suspension catholyte is designed and prepared based on polyvinylpyrrolidone (PVP) functionalized Sulfur-Ketjenblack-Graphene composite (S-KB-G@P). Amphiphilic PVP is anchored onto the surface of graphene to enhance contact between polar sulfur species and conductive network constructed by nonpolar graphene and KB, and then facilitate the redox reaction of sulfur catholyte. Meanwhile, anchored PVP endows S-KB-G nanoparticles with well-dispersed characteristics, which reduces the viscosity and accelerates the ion transfer in highly concentrated S-KB-G@P suspension. The S-KB-G@P suspension catholyte exhibits high sulfur utilization of 89.5% and volumetric energy of 718 W h L −1 ; moreover, high energy density of 445 W h L −1 and excellent cycle stability are achieved at −30 °C. Verified in a laboratory flow cell, the strategy offers a new opportunity to develop high-energy flow batteries by amphiphilic functionalization in cold-climate region. Graphical abstract: PVP is utilized to improve the sulfur utilization of suspension catholyte. Amphiphilic PVP enhances the contact between polar sulfur species and nonpolar carbon carrier, and meanwhile endows the sulfur suspension with satisfactory rheological properties. The demonstrated lithium-sulfur flow cell exhibits high energy density and excellent cycle performance at −30 °C. Image 1 Highlights: A new strategy is proposed to improve the sulfur utilization of sulfur suspension catholyte. Amphiphilic PVP is adopted to functionalize sulfur suspension catholyte. The demonstrated sulfur suspension catholyte exhibits high energy density and excellent low-temperature performance. The feasibility of the amphiphilic-functionalized sulfur suspension catholyte is verified in varied flow modes.